2014
DOI: 10.1159/000360416
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dexamethasone Exposure Inhibits the Gonadotropin-Releasing Hormone Neuronal Movement in the Preoptic Area of Rat Offspring

Abstract: Migration and final positioning of gonadotropin-releasing hormone (GnRH) neurons in the preoptic area (POA) is critical for reproduction. It is known that maternal dexamethasone (DEX) exposure impairs reproductive function and behaviour in the offspring. However, it is still not known whether maternal DEX exposure affects the postnatal GnRH neurons in the offspring. This study determined the neuronal movement of enhanced green fluorescent protein (EGFP)-tagged GnRH neurons in slice culture of postnatal day 0 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Time-lapse image analysis of rat embryonic E14–GnRH neurons between the nasal and brain compartments showed movement of GnRH neurons at a velocity of 9–13 μm/h in brain slice cultures similar to E13 GnRH neurons in embryonic mouse nasal explants culture migrating at a velocity of 12–13 μm/h ( 38 ). On the other hand, our recent time-lapse imaging study of rat GnRH neurons on postnatal day 0 and day 5 showed movement of GnRH neurons at a velocity of 3–5 μm/h ( 39 ). This suggests that rat embryonic GnRH neurons have high motility and, therefore, may be a good model to determine intracellular signaling for cellular movement.…”
Section: Discussionmentioning
confidence: 99%
“…Time-lapse image analysis of rat embryonic E14–GnRH neurons between the nasal and brain compartments showed movement of GnRH neurons at a velocity of 9–13 μm/h in brain slice cultures similar to E13 GnRH neurons in embryonic mouse nasal explants culture migrating at a velocity of 12–13 μm/h ( 38 ). On the other hand, our recent time-lapse imaging study of rat GnRH neurons on postnatal day 0 and day 5 showed movement of GnRH neurons at a velocity of 3–5 μm/h ( 39 ). This suggests that rat embryonic GnRH neurons have high motility and, therefore, may be a good model to determine intracellular signaling for cellular movement.…”
Section: Discussionmentioning
confidence: 99%